Analysis of the Decision of the State Administrative Court Number 604/G/2023/PTUN.JKT Concerning Government Actions in the Field of Administrative Law from the Perspective of Gustav Radbruch - Maarif, Rizal Syamsul; Dhafin Riyasy Ishak; Devina Mayra Purnama; Rezza Syah Fahleffi (JURNAL ILMIAH LIVING LAW, 2025)
The Jakarta State Administrative Court (PTUN) Decision Number 604/G/2023/PTUN.JKT which granted part of Anwar Usman's lawsuit against the Constitutional Court has caused controversy in the Indonesian constitutional legal order. The main problem lies in the limits of the PTUN's jurisdiction over constitutional judicial institutions and the validity of administrative intervention into the internal mechanisms of the Constitutional Court. This article aims to analyze the decision based on Gustav Radbruch's legal theory, which emphasizes the balance between justice, legal certainty, and utility as basic principles in the legal system. This study uses a juridical-normative method with a conceptual approach and a legal philosophy approach to examine the alignment of the substance of the decision with universal legal values. The results of the analysis show that the PTUN decision No. 604/G/2023/PTUN.JKT does not reflect the principle of substantive justice because it ignores the institutional autonomy of the Constitutional Court and opens up space for horizontal intervention between state institutions. From the aspect of legal certainty, this decision creates jurisdictional ambiguity that threatens the stability of the constitutional system. Meanwhile, from the perspective of utility, the decision is considered counterproductive because it has the potential to weaken the integrity and effectiveness of the Constitutional Court's role as a guardian of the constitution. Therefore, this article recommends affirming the limits of administrative court jurisdiction over constitutional institutions, as well as strengthening the ethical approach in the practice of state administrative law so as not to be trapped in narrow legal positivism